Involvement of neuronal factors in tumor angiogenesis and the shaping of the cancer microenvironment - Shalabi, Sharif; Belayachi, Ali; Larrivée, Bruno (Frontiers in Immunology, 2024)
Emerging evidence suggests that nerves within the tumor microenvironment play a crucial role in regulating angiogenesis. Neurotransmitters and neuropeptides released by nerves can interact with nearby blood vessels and tumor cells, influencing their behavior and modulating the angiogenic response. Moreover, nerve-derived signals may activate signaling pathways that enhance the production of pro-angiogenic factors within the tumor microenvironment, further supporting blood vessel growth around tumors. The intricate network of communication between neural constituents and the vascular system accentuates the potential of therapeutically targeting neural-mediated pathways as an innovative strategy to modulate tumor angiogenesis and, consequently, neoplastic proliferation. Hereby, we review studies that evaluate the precise molecular interplay and the potential clinical ramifications of manipulating neural elements for the purpose of antiangiogenic therapeutics within the scope of cancer treatment.